Firm Size and Credit in Argentina - Sebastian Auguste; Ricardo N. Bebczuk; Gabriel Sanchez (Inter-American Development Bank (IDB), 2013)
The goal of this paper is to study the link between bank credit (and internal funding) and average firm size in Argentina. Besides the fact that economic growth tends to go hand in hand with larger firm size, the topic is of particular interest because of the severe credit crunch in Argentina in the aftermath of the 2001-2002 financial crisis. To this end, a novel three-digit industry-level dataset spanning the 2000-2010 period was constructed. The results confirm the expected positive impact of credit supply on average firm size. Furthermore, the study expands on common knowledge by testing the sensitivity of firm size to internal funding and the differential financing behavior of the primary and the manufacturing sector. The results do not seem to be driven by endogeneity bias.
Keywords: D22; D23; G21; G32; 330